The Effect Of Creativity And Innovation On Competitive Advantage (Case Study On Business Personnel Of Bata Business In The Sub-District Of Pematang Kaseh Perbaungan) - Dewi Suma; Budi Alamsyah Siregar (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effects of creativity and innovation on competitive advantage (a case study on brick business actors in PEMATANG KASEH PERBAUNGAN DISTRICT). The sample used is 70 brick business entrepreneurs in Hinai District. The data collection used is using general information given to respondents. The data is processed using SPSS 20.0 For Windows. The analysis technique used is multiple linear regression using the formula Y = a+b1x1+b2x2+e. The results of this research are the influence given by creativity to competitive advantage as much as 0.264, and the positive is that the greater the creativity, the greater the interest in using competitive advantage (Y). tcount at = 3,209 > T table = 1,994 or using comparing the value of sig = 0.000 < level xss=removed xss=removed> T table = 1.994 or using comparing the value of sig = 0.000 < error rate 5% = 0.05 it can be concluded that Innovation to Competitive Advantage. the effect given is positive; the beta value indicates this obtained positive 0.645.